PERANCANGAN ULANG TATA LETAK STORE DI PT INDOMARCO PRISMATAMA DENGAN METODE ABC - JAENAL ABIDIN; KAREL L. MANDAGIE; W. TEDJA BHIRAWA (JURNAL TEKNIK INDUSTRI, 2021)
PT. Indomarco Prismatama is a retail company located in Jakarta with household needs products. The problems faced are irregularities in product placement, this will impede the search process so that the utilization of space becomes less effective and many do not conform to warehouse layout system, it will be done improvement of warehouse layout with ABC method. This research is done by collecting extensive data Warehouse area, carton dimensions on each product, material handling dimensions, data entry and data out in the period of August- December 2019. Then calculate the development of warehouse needs covering the needs of storage space, area of warehouse, the activity of each pickup, the calculation of distances with rectilinear distance method and classification of goods based on the frequency of ABC analysis. The result of the calculation of the initial storage area of 71.06 m2 and the storage area of the proposed 30 94m2 with an efficiency of 56.45%, wide-pickup aisle 1m and the main aisle 2m, with analysis method ABC can minimize the mileage of material handling from the average per month in the initial layout conditions of the approximate distance is 1454, 6m/month after the layout changes made with the analysis method of ABC to 574, 1m/month with efficiency 60.5%.